Hexahydro-1,2,3-triazine Derivatives: Synthesis, Antimicrobial Evaluation, Antibiofilm Activity and Study of Molecular Docking Against Glucosamine-6-Phosphate - Nabel Bunyan Ayrim; Fadhel Rukhis Hafedh; Yasir Mohamed Kadhim; Abduljabbar Sabah Hussein; Ahmed Mutanabbi Abdula; Ghosoun Lafta Mohsen; Mohammed Mahdi Sami (Indonesian Journal of Chemistry, 2024)
The N,N',N''-trisubstituted hexahydro-1,3,5-triazine derivatives (3a–g) had been created and identified through infrared, nuclear magnetic resonance, and mass spectrometry according to their symmetric basic structure. Three molecules of diverse aromatic amines and three molecules of formaldehyde were assembled in a "1+1+1+1+1+1" condensation reaction to produce hexahydrotriazines. Two Gram-positive (Staphylococcus aureus, Staphylococcus epidermidis) and two Gram-negative (Klebsiella pneumonia, Pseudomonas aeruginosa) bacteria were used to evaluate the antimicrobial activity of the produced compounds. The anti-biofilm activity of 3g against S. aureus was also examined. In this investigation, glucosamine-6-phosphate synthase was employed to investigate the binding affinity of 3g within the enzyme's binding site. The results demonstrated that most of the synthesized hexahydro-1,3,5-triazine compounds have mild antimicrobial effects in comparison with the commonly used drug ampicillin, whereas the compounds 3g are potentially anti-biofilm agents. Molecular docking with the Autodock 4.2 tool was applied to study the binding affinity. It was found to hit (3g) in the active center of glucosamine-6-phosphate synthase as the target enzyme for antimicrobial agents. In silico studies reveal that the discovered hit is a promising glucosamine-6-phosphate inhibitor, as well as that the docking data matched up to the in vitro assay.